2020
DOI: 10.1093/cid/ciaa1463
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Hemophagocytic Lymphohistiocytosis HScore in Patients With Coronavirus Disease 2019

Abstract: The clinical manifestation of moderate to severe COVID-19 has parallels to secondary haemophagocytic lymphohistiocytosis (HLH) both clinically and based on molecular inflammatory response. We found no evidence to support the utility of risk stratifying COVID-19 patients using risk scoring methodology designed for HLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…In children with MIS-C there was a significant reduction of lymphocytes and platelets as compared to the COVID-19 group. Notably lymphopenia and thrombocytopenia are also typical of the hyperinflammatory form of COVID-19 in adults (7,12). The analysis of the plasmatic levels of inflammatory chemokines and cytokines in patients with COVID-19 and MIS-C showed higher levels of IL-6, CXCL8, CCL2/MCP-1, CXCL9/MIG, and CXCL10/IP-10 in MIS-C, whereas CCL5 levels were significantly higher in the COVID-19 group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In children with MIS-C there was a significant reduction of lymphocytes and platelets as compared to the COVID-19 group. Notably lymphopenia and thrombocytopenia are also typical of the hyperinflammatory form of COVID-19 in adults (7,12). The analysis of the plasmatic levels of inflammatory chemokines and cytokines in patients with COVID-19 and MIS-C showed higher levels of IL-6, CXCL8, CCL2/MCP-1, CXCL9/MIG, and CXCL10/IP-10 in MIS-C, whereas CCL5 levels were significantly higher in the COVID-19 group.…”
Section: Discussionmentioning
confidence: 93%
“…In children with MIS-C there was a significant reduction of lymphocytes and platelets as compared to the COVID-19 group. Notably lymphopenia and thrombocytopenia are also typical of the hyperinflammatory form of COVID-19 in adults ( 7 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 patients studied by Lorenz et al, only one patient reached a threshold >169 in the absence of the bone marrow aspirate criterion and six patients reached a threshold >169 if the bone marrow aspirate criterion was assumed positive [ 172 ]. Clark et al retrospectively reviewed 152 patients with polymerase chain reaction confirmed COVID-19 patients and demonstrated a median HScore of 52, with the majority of patients not reaching sufficient thresholds for an HLH diagnosis, although notably, many variables were missing including 46 patients who did not have ferritin levels and no patients having bone marrow biopsies collected [ 174 ]. These studies raise the question of the utility of the HScore in COVID-19 patients and highlight a need for more specific, accessible means of identifying HLH.…”
Section: Covid-19: Secondary Hlh Sepsis or Hlh-sepsis Overlap?mentioning
confidence: 99%
“…Persistent infection-induced inflammation is a shared feature of COVID-19 and XLP-2. Though caused by different viruses (EBV versus SARS-CoV-2) and the clinical syndromes of COVID-19 being distinct from the HLH of XLP-2 [151,152], inflammatory cell death likely represents a turning point from infection to irreversible inflammation in both COVID-19 and XLP-2.…”
Section: Therapeutic Implications For Covid-19mentioning
confidence: 99%